Hubungan Antara Onset Terjadinya Menopause Dengan Status Perkawinan - Katarina Bernadet Dinda Sekar Melati (Nexus Biomedika, 2012)
Background: Elderly women will experience a condition due to the aging process called menopause. The onset of menopause in one woman to the others is diverse depending on its modifying factors. Marital status is suspected as one of modifying factors besides the environmental factors like pollution and radiation, smoking, obesity, numbers of children and chemotherapy. Bogor, one of the city in West Java, has 452 women with unmarried status which are on the edge of menopause. This purpose of this research is to understand the correlation between onset of menopause and marital status. Methods: This research used analytical observational studies with cross sectional approach by using purposive sampling technique which had been done in June until July 2011. The number of samples was 60 women coming from six region of Bogor who were appropriate to the required inclusion criteria. The data was collected through interviewing and answering the questionnaire by respondent. The data as a result were analyzed statistically by Chi Square analysis by using SPSS 17.0. Results: The result of Chi Square analysis was 4,286 as X2 count. This result was more than X2 table for the standard of significance 5% and the degree of freedom 1, which was 3,841 (p<0,05). From counting of Odds Ratio (OR) the result was 3. Conclusions:. There was a relation between onset of menopause and marital status. Unmarried woman would face early menopause onset three times higher than the married ones. Keywords: Onset of Menopause Marital Status